The Big-Fish-Little-Pond Effect on Academic Self-Concept: A Meta-Analysis - Fang, Junyan; Huang, Xitong; Zhang, Minqiang; Huang, Feifei; Li, Zhe; Yuan, Qiting (Frontiers in Psychology, 2018)
The Big-fish-little-Pond effect is well acknowledged as the negative effect of class/school average achievement on student academic self-concept, which profoundly impacts student academic performance and mental development. Although a few studies have been done with regard to this effect, inconsistence exists in the effect size with little success in finding moderators. Here, we present a meta-analysis to synthesize related literatures to reach a summary conclusion on the BFLPE. Furthermore, student age, comparison target, academic self-concept domain, student location, sample size, and publication year were examined as potential moderators. 33 studies with 56 effect sizes (total N=1,276,838) were finally included. The random effects model led to a mean of the BFLPE at β= -.28 (p<0.001). Moreover, moderator analyses revealed that the Big-Fish-Little-Pond effect is an age-based process and an intercultural phenomenon, which is stronger among high school students, in Asia and when verbal self-concept is considered. This meta-analysis is the first quantitative systematic overview of BFLPE, whose results are valuable to the understanding of BFLPE and reveal the necessity for educators from all countries to learn about operative means to help students avoid the potential negative effect. Future research expectations are offered subsequently.